Fostering sustainable development in the age of technologies - Sharma, Rohit,; Shishodia, Anjali,; Gupta, Ashish, (Emerald Publishing Limited, 2023)
The world is changing at an unprecedented pace and organizations worldwide are finding it difficult to match their operational efficiency and sustainable development targets with the United Nations Sustainable Development Goals (UNSDGs). Due to massive scarcity of resources, global supply chains are under immense pressure, leading to social, economic, and environmental challenges. Holistic sustainable development across social, economic, and environmental dimensions to create an equitable society varies widely in its efficiency towards creating a resilient and inclusive future. Fostering Sustainable Development in the Age of Technologies highlights the interplay between various disruptive technologies such as Artificial Intelligence, Autonomous robots, Big Data Analytics, Blockchain, Cloud Computing, and Digital Twins, and holistic sustainable development. In the highly dynamic business environment, there is an urgent need to catch up with the paradigm shift being created using these technologies. The studies brought together here emphasise how various disruptive technologies can aid in sustainable development, offering possible strategies to help tackle the challenges we face today and embrace the new normal. Collaboration, adaptation, and continuous learning hold the key in overcoming the grand societal challenges and maintaining a balance between social, economic, and environmental dimensions. This edited collection appeals to a wide range of academics and professionals including graduate, postgraduate, and PhD research scholars, and faculty members in the areas of International Management, International Business, International Marketing, Finance, Human Resources and Corporate Governance. They are also of interest to Government Agencies, Practicing Managers, Research Agencies, and Libraries of Business Management Colleges and Universities.